Role of Genetic Factors in the Cause of Alzheimer’s Disease: Literature Review - Al-Qazzaz, Halah Kamal (American Journal of Biology and Natural Sciences, 2025)
Alzheimer’s disease (AD) is a chronic, progressive neurological disorder that primarily affects older adults, accounts for 1 to 5% of all cases, and is the leading cause of death worldwide, with a dominant familial or autosomal presentation. It accounts for 1 to 5% of all cases and is the leading cause of death worldwide. This review discusses the current understanding of the relationship between genetically related and environmental influences closely associated with the development of neurodegeneration, as well as the pathophysiology of AD, which is the pathological accumulation of multifactorial etiology, significantly contributing to the development of genetic and non-genetic factors. The alteration of pathologic amyloid-beta (Aβ) plaques and neurofibrillary tangles leads to extensive neuronal damage, greatly compromising daily functioning and quality of life, which causes dementia in older persons. It has complex symptoms and influences the development of both affective factors. Genetic factors account for approximately 60-80% of AD risk, with specific genes such as apolipoprotein E (APOE), amyloid precursor protein (APP), presenilin 1 (PSEN1), and presenilin 2 (PSEN2) being crucial in both early- and late-onset forms of the disease. Early biomarkers are necessary to advance diagnostic methods and identify effective therapeutic targets for AD.